2017
DOI: 10.1186/s12936-017-1955-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to two new Lactococcus lactis-produced recombinant Pfs48/45 and Pfs230 proteins increase with age in malaria patients living in the Central Region of Ghana

Abstract: BackgroundRecent advances in malaria control efforts have led to an increased number of national malaria control programmes implementing pre-elimination measures and demonstrated the need to develop new tools to track and control malaria transmission. Key to understanding transmission is monitoring the prevalence and immune response against the sexual stages of the parasite, known as gametocytes, which are responsible for transmission. Sexual-stage specific antigens, Pfs230 and Pfs48/45, have been identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 34 publications
(50 reference statements)
1
48
1
Order By: Relevance
“…Studies on various fragments of this region, expressed in a wheat germ cell-free expression system, also indicated that the N-terminal subdomain (aa 443 to 588) was sufficient to induce transmission-blocking activity (87). Higher concentrations of antibodies against this subdomain were found to correlate positively with the age of the host in a preliminary study and were not affected by deletion of one of the two "YGE" tripeptides (85). Optimization using the Pichia pastoris expression system identified recombinant Pfs230 aa 443 to 730 (Pfs230D1M) as a strong transmission-blocking vaccine candidate, and two formulations (Pfs230D1M conjugated to exoprotein A [Pfs230D1M-EPA]), one with aluminum hydroxide (Alhydrogel) (ClinicalTrials registration no.…”
Section: Gametocyte/gamete Antigens Pfs230 Pfs48/45 Pfs47 and Hap2mentioning
confidence: 94%
See 1 more Smart Citation
“…Studies on various fragments of this region, expressed in a wheat germ cell-free expression system, also indicated that the N-terminal subdomain (aa 443 to 588) was sufficient to induce transmission-blocking activity (87). Higher concentrations of antibodies against this subdomain were found to correlate positively with the age of the host in a preliminary study and were not affected by deletion of one of the two "YGE" tripeptides (85). Optimization using the Pichia pastoris expression system identified recombinant Pfs230 aa 443 to 730 (Pfs230D1M) as a strong transmission-blocking vaccine candidate, and two formulations (Pfs230D1M conjugated to exoprotein A [Pfs230D1M-EPA]), one with aluminum hydroxide (Alhydrogel) (ClinicalTrials registration no.…”
Section: Gametocyte/gamete Antigens Pfs230 Pfs48/45 Pfs47 and Hap2mentioning
confidence: 94%
“…Pfs230 contains 14 s48/45 6-Cys domains (67), which is the maximum number that has been found among members of the 6-Cys s48/45 family (74). The numerous cysteine motif domains of the protein have made expression of full-length, correctly folded, soluble protein difficult, but fragment expression has been achieved (85)(86)(87). Through the expression of various maltose binding protein (MBP)-tagged fragments of Pfs230 in Escherichia coli, antibodies generated against a region designated "C" (aa 443 to 1132) were found to reduce transmissibility to mosquitoes by as much as 80% (88).…”
Section: Gametocyte/gamete Antigens Pfs230 Pfs48/45 Pfs47 and Hap2mentioning
confidence: 99%
“…Antibody responses including IgG, IgM, IgG1, and IgG3 against recombinant P. falciparum sexual stage and asexual stage antigens were quantified using an indirect ELISA protocol [41]. The antigens used in this study include Pfs230 [14] and MSP3 [30] produced in Lactococcus lactis. Briefly Pfs230 antigen was diluted to 1 µg/ ml in carbonate buffer [14,15] and MSP3 diluted to 1 µg/ ml in phosphate-buffered saline (1X PBS, pH7.2) [15,30] and 100 µl/well of the diluted antigen was used to coat the wells of Maxisorp NUNC plates (Nunc Maxisorp, UK) overnight at 4 °C.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…The antigens used in this study include Pfs230 [14] and MSP3 [30] produced in Lactococcus lactis. Briefly Pfs230 antigen was diluted to 1 µg/ ml in carbonate buffer [14,15] and MSP3 diluted to 1 µg/ ml in phosphate-buffered saline (1X PBS, pH7.2) [15,30] and 100 µl/well of the diluted antigen was used to coat the wells of Maxisorp NUNC plates (Nunc Maxisorp, UK) overnight at 4 °C. The plates were subsequently washed with wash buffer (PBST; 1X PBS supplemented with 0.05% Tween 20 at pH7.2), blocked with 3% nonfat skimmed milk (Marvel, UK) in1X PBS and incubated at room temperature (RT) for 1 h. The plates were then incubated with 100 µl/well of plasma diluted to 1:200 for IgG and IgM and 1:100 for IgG1 and IgG3 in 1% of non-fat skimmed milk in 1X PBS.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
See 1 more Smart Citation